Sustained‐release dexamethasone for the treatment of ocular inflammation and pain after cataract surgery. Issue 10 (October 2015) - Walters, Thomas; Endl, Michael; Elmer, Thomas R.; Levenson, Jeffrey; Majmudar, Parag; Masket, Samuel
Abstract : Purpose : To evaluate the safety and efficacy of dexamethasone as a sustained‐release drug depot when placed in the canaliculus for the treatment of ocular inflammation and pain in cataract surgery patients. Setting : Four private practice sites in the United States. Design : Multicenter randomized double‐masked clinical trial. Methods : Patients were randomized (1:1) to receive either the sustained‐release dexamethasone or a placebo vehicle punctum plug inserted into the inferior distal canaliculus of the operated eye intraoperatively during cataract surgery. The primary endpoints were the proportions of patients with absence of cells or pain in the anterior chamber at 8 days. Secondary endpoints included cells, flare, pain, and the presence of the device at various timepoints through 30 days. Results : Approximately one fifth (20.7%) of patients in the sustained‐release dexamethasone group had an absence of anterior chamber cells at 8 days compared with 10.0% in the placebo group ( P = .1495). A higher proportion of patients in the sustained‐release dexamethasone group (79.3%) than in the placebo group (30.0%) had an absence of ocular pain at 8 days ( P < .0001) and at all other timepoints ( P < .0002). There were significantly higher proportions of patients in the sustained‐release dexamethasone group than in the placebo group with an absence of anterior chamber cells, anterior chamber flare, and pain at several timepoints through 30 days ( P ≤ .0251). Conclusion : Sustained‐release dexamethasone provided elution of drug for up to 1 month after cataract surgery, providing clinically significant reductions in inflammation and pain. Financial Disclosure : Dr. Masket is a consultant to and shareholder in Ocular Therapeutix, Inc. No other author has a financial or proprietary interest in any material or method mentioned.